Demographic development of breeding populations of yellow-legged gull Larus michahellis Naumann, 1840 on the small islands and along the coastline of Numidia (north-eastern Algeria) - S. Telailia; L. Boutabia; E. Bensaci; A. Boucheker; M. F. Samar; M. C. Maazi; M. Saheb; M. A. Bensouilah; M. Houhamdi (Journal of Animal and Plant Sciences, 2015)
The Yellow-legged gull (Larus michahellis), like most Laridae, has increased in number significantly over the 20th century. One of the major causes of this demographic explosion is supply by humans of abundant food resources through easily accessible open landfill sites. The objective of the study is to assess on a regional scale, the size of colonies of Yellow-legged gull and population dynamics. Yellow-legged gull population of Numidia had shown growth of 2.01% as compared to 1978. The average annual reproductive rate ( ) is 1.03 Overall in study area. The highest density was observed on Srigina Island, with 106.7 pairs per hectare, followed by that of the Cap de Fer islet with 105 pairs per hectare, the Saint Piastre island with 93.3 pairs per hectare and that of the Lions islet with 80 pairs per hectare. The Yellow-legged gull exhibits early nesting on islands where the surface area is greater than one hectare, such as Srigina Island and Saint Piastre Island The study conducted in Numidia has allowed us to bring the latest information on the breeding populations of Yellow-legged gull at the local scale (Algeria) which remained unknown for nearly three decades. The data presented are compatible with most Mediterranean colonies.
Keywords: Yellow-legged gull; Laridae; demography; food resources; Numidia; Algeria